Relationship of Knowledge and Family Support to Exclusive Breastfeeding for Working Mothers (Prodi DIII Kebidanan Blora Poltekkes Kemenkes Semarang, 2019)
Breastfeeding for infants is the best way of feeding, especially for infants less than six months old. Exclusive breastfeeding for six months has been shown to have many benefits. Although the benefits of breastfeeding have been published around the world, exclusive breastfeeding coverage rates are still far from expected. For working mothers giving exclusive breastfeeding is not easy. The purpose of this study was to determine the relationship of knowledge and family support to exclusive breastfeeding for working mothers. This type of observational analytic study uses atime approach cross sectional. The sample in this study is mothers who have babies aged 6-24 months who work in government agencies in the Blora Regency. The sampling technique using total sampling, as many as 30 respondents. The level of mother's knowledge and family support was measured using a questionnaire. Test data analysis using the Chi-Square test. Based on the results of data analysis, there is no relationship between the level of knowledge with exclusive breastfeeding for working mothers (p = 0.675 0.05) and there is a relationship between family support and exclusive breastfeeding for working mothers (p = 0.001 0.05) . The conclusion of this study is that there is no relationship between the level of knowledge with exclusive breastfeeding for working mothers and there is a relationship between family support and exclusive breastfeeding for working mothers.